2012
DOI: 10.1136/emermed-2011-200757
|View full text |Cite
|
Sign up to set email alerts
|

Improving paediatric pain management: introducing the ‘Pain Passport’

Abstract: The 'Pain Passport' is a novel method of improving the management of pain in children. It consists of a leaflet carried by the patient which records serial pain scores. It attempts to empower patients and prompt medical and nursing staff to evaluate the child's pain. Preliminary audit data in support of this concept are encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…The most important variables impacting on parent satisfaction with ED care are being informed about delays, nurse attention to the patient's needs and pain management . Interventions to improve pain management have included specific management protocols (including staff education), a ‘Pain Passport’ and a NIA pathway . These studies decreased times to analgesia and increased rates of pain assessment and reassessment.…”
Section: Discussionmentioning
confidence: 99%
“…The most important variables impacting on parent satisfaction with ED care are being informed about delays, nurse attention to the patient's needs and pain management . Interventions to improve pain management have included specific management protocols (including staff education), a ‘Pain Passport’ and a NIA pathway . These studies decreased times to analgesia and increased rates of pain assessment and reassessment.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the Pain Passport consisted of pain scoring explanations (the Wong-Baker Pain Scale [WBPS] and Numeric Rating Scale [NRS]); three boxes to record pain scores three times, including (1) at ED arrival, (2) half an hour after analgesic administration, and (3) upon discharge; and an additional colouring and puzzle page [7]. In our study, the leaflet consisted of four pages, and although only the Korean version of the Pain Passport was used in this study, a translated version of the Pain Passport is shown for readers in Fig.…”
Section: Developing a Modified Version Of The Pain Passport For Pain mentioning
confidence: 99%
“…The "Pain Passport" can serve as a tool for achieving patient-centred pain management. The Pain Passport is a self-reported pain sheet on which the patient or caregiver directly records the degree of pain to help put the child in charge of his or her analgesic needs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Comparability of the pre-post cohorts was difficult to assess in 10 studies (Boyd & Stuart, 2005;Eisen & Amiel, 2007;Habich & Letizia, 2015;Jadav et al, 2009;LeMay et al, 2009;LeMay et al, 2010;Newstead et al, 2013;Porter et al, 2015;Ramira et al, 2016;Taylor et al, 2013) because baseline characteristics were inadequately reported, inequality in group diagnoses, age or causation of pain and/or the small numbers of participants recruited. Ten studies reported consecutive participant selection (Boyd & Stuart, 2005;Hawkes et al, 2008;Iyer et al, 2011;Jadav et al, 2009;Kaplan et al, 2008;Porter et al, 2015;Ramira et al, 2016;Scott et al, 2013;Somers et al, 2001;Williams et al, 2012) while in the remaining studies the selection process was unclear, or numbers too small to be representative of the population.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The method of data collection was considered in each of the studies. Eleven studies utilised retrospective data collection (Habich & Letizia, 2015;Hawkes et al, 2008;Iyer et al, 2011;Jadav et al, 2009;Kaplan et al, 2008;Newstead et al, 2013;Ramira et al, 2016;Santervas et al, 2010;Scott et al, 2013;Somers et al, 2001;Williams et al, 2012), seven studies collected data prospectively (Boyd & Stuart, 2005;Brent et al, 2009;Corwin et al, 2012;LeMay et al, 2009;LeMay et al, 2010;Tanabe et al, 2002;Taylor et al, 2013), and two studies used a combination (Eisen & Amiel, 2007;Porter et al, 2015). Authors acknowledged that retrospective data collection has the potential to undermine validity, given the reliance on the accuracy and completeness of patient charts.…”
Section: Inclusion Criteriamentioning
confidence: 99%